(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The purpose of this article was to investigate the effects of psychomotor training on specific psychomotor variables of young female basketball players. Thirty female basketball players in all were chosen at random for the study and split equally into two groups: the Experimental Group and the Control Group. Over the course of six weeks, the experimental group received psychomotor training three times a week (on Mondays, Wednesdays, and Fridays) for forty to forty-five minutes. No training of any kind was given to the control group. The three dependent variable’s rhythmic ability, balance ability, and response ability were evaluated for each person. Descriptive statistics and a paired t-test were used to analyze the data at the significance level of 0.05. The study’s findings revealed that while the control group did not experience any improvements, the young basketball players who received motor skill training for six weeks experienced an improvement in their psychomotor development.